Incident Mycobacterium tuberculosis infection in household contacts of infectious tuberculosis patients in Brazil - Jones-López, Edward C. (BMC Infect Dis, 2017)
BACKGROUND: In household contact investigations of tuberculosis (TB), a second tuberculin skin test (TST) obtained several weeks after a first negative result consistently identifies individuals that undergo TST conversion. It remains unclear whether this delay in M. tuberculosis infection is related to differences in the infectious exposure, TST boosting, partial host resistance, or some other factor. METHODS: We conducted a household contact study Vitória, Brazil. Between 2008 and 2013, we identified culture-positive pulmonary TB patients and evaluated their household contacts with both a TST and interferon gamma release assay (IGRA), and identified TST converters at 8–12 weeks post study enrollment. Contacts were classified as TST-positive (≥10 mm) at baseline, TST converters, or persistently TST-negative. We compared TST converters to TST-positive and to TST-negative contacts separately, using generalized estimating equations. RESULTS: We enrolled 160 index patients and 838 contacts; 523 (62.4%) were TST+, 62 (7.4%) TST converters, and 253 (30.2%) TST−. TST converters were frequently IGRA− at 8–12 weeks. In adjusted analyses, characteristics distinguishing TST converters from TST+ contacts (no contact with another TB patient and residence ownership) were different than those differentiating them from TST− contacts (stronger cough in index patient and contact BCG scar). CONCLUSIONS: The individual risk and timing of M. tuberculosis infection within households is variable and dependent on index patient, contact and environmental factors within the household, and the surrounding community. Our findings suggest a threshold effect in the risk of infection in humans. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-017-2675-3) contains supplementary material, which is available to authorized users.